Experimental determination and thermodynamic modeling of solid–liquid equilibria in the system NaCl–Na2SO4–H3BO3–H2O at 323.15 K and its application in industry. (July 2022) - Sun, Shuaiqi; Li, Dan; Zhang, Tao; Ma, Yong; Meng, Lingzong; Deng, Tianlong; Guo, Yafei
Graphical abstract: Highlights: The solubilities in systems NaCl–H3 BO3 –H2 O and NaCl–Na2 SO4 –H3 BO3 –H2 O were studied. The Pitzer thermodynamic model of the two systems was constructed. The phase diagram and Pitzer model were used for simulation of H3 BO3 separation. Abstract: The solubilities and refractive indices in the systems NaCl–Na2 SO4 –H3 BO3 –H2 O and NaCl–H3 BO3 –H2 O at 323.15 K were investigated with the isothermal dissolution equilibrium method. The phase diagram of the ternary system consists of two single-salt crystallization fields of NaCl and H3 BO3, two solubility univariant curves, and one invariant point. The dry-salt diagram of the quaternary system is composed of three single-salt crystallization fields corresponding to NaCl, Na2 SO4 and H3 BO3, three solubility univariant curves, and one invariant point. A comparison of the diagrams of the quaternary system at (298.15, 323.15 and 373.15) K shows that areas of sodium chloride and sodium sulfate salts region increases whereas the area of H3 BO3 region decreases distinctly with temperature increasing. Combining the Pitzer parameters and solubilities in the ternary systems in this study and literatures, the lacking Pitzer parameters for H3 BO3 were fitted on the basis of Pitzer model. The calculated solubilities with the model agree well with the experimental data. The phase diagrams and Pitzer model for the quaternary system at 298.15 and 323.15 K were then used to conduct a computer simulation of brine separation. All H3 BO3 and most of Na2 SO4 can be separated from the solution with segmental evaporation method.